Effect of a controlled sub-seabed release of CO2 on the biogeochemistry of shallow marine sediments, their pore waters, and the overlying water column. (July 2015) - Lichtschlag, Anna; James, Rachael H.; Stahl, Henrik; Connelly, Doug
Highlights: Field-scale sub-seabed release experiment to simulate leakage from CO2 reservoir. CO2 induces pronounced changes in pore water geochemistry. Dissolution of minerals as a result of increased dissolved CO2 concentrations. Changes in pore water geochemistry are transient and spatially restricted. Levels of released metals are low and likely to have minor impact on benthic ecosystems. Abstract: The potential for leakage of CO2 from a storage reservoir into the overlying marine sediments and into the water column and the impacts on benthic ecosystems are major challenges associated with carbon capture and storage (CCS) in subseafloor reservoirs. We have conducted a field-scale controlled CO2 release experiment in shallow, unconsolidated marine sediments, and documented the changes to the chemical composition of the sediments, their pore waters and overlying water column before, during and up to 1 year after the 37-day long CO2 release. Increased levels of dissolved inorganic carbon (DIC) were detected in the pore waters close to the sediment-seawater interface in sediments sampled closest to the subsurface injection point within 5 weeks of the start of the CO2 release. Highest DIC concentrations (28.8 mmol L −1, compared to background levels of 2.4 mmol L −1 ) were observed 6 days after the injection had stopped. The high DIC pore waters have high total alkalinity, and low δ 13 CDIC values (−20‰, compared to a background value of −2‰), due to the dissolution of the injected CO2 ( δ 13 C = −26.6‰). The high DIC pore waters have enhanced concentrations of metals (including Ca, Fe, Mn) and dissolved silicon, relative to non-DIC enriched pore waters, indicating that dissolution of injected CO2 promotes dissolution of carbonate and silicate minerals. However, in this experiment, the pore water metal concentrations did not exceed levels considered to be harmful to the environment. The spatial extent of the impact of the injected CO2 in the sediments and pore waters was restricted to an area within 25 m of the injection point, and no impact was observed in the overlying water column. Concentrations of all pore water constituents returned to background values within 18 days after the CO2 injection was stopped.